Maurice Ravel and Exoticism. A study of the exotic in he vocal works of Maurice Ravel with special reference to L'Enfant et les sortileges and the Trois Chansons Madecasses - Serfontein, Andre (College of Music, 2014)
The fascination for things exotic or fairytale-like occupied Ravel throughout his entre life. In fact, one can safely assume that these fascinations may have prevented him from forming some sort of mental inertia in those difficult years for him following the First World War. On writing about his Shéhárazade triptych, Ravel stated : ... in them, I have succumbed again to the profound fascination which the East has held for me since childhood.""""' That is the purpose of this dissertation : to examine Ravel's handling and incorporation of this fascination into his works for solo voice. Ravel, within the confines of his genius has succeeded magnificently in exploiting the various timbres capable on his chosen instruments; and sought timbres from the instrumentation commissioned from him (as in the case of the Chansons madécasses ) to assimilate unexplored, exotic colours. Naturally, since Ravel experienced the tail end of an exotic rage that swept through Europe at the turn of the century, a survey was made of its origins in Europe. The musical references to Sharerazade in Chapter Two correspond to the piano and vocal score published by Dover Publications, while other musical examples in this chapter, from the Sonatina, the String Quartet and the Introduction and Allegro are taken from the Durand Edition, published in 1905, 1906 and 1910 respectively. *Pierre Bemac. The interpretation of French Song. London: Victor Gollanncz, 1976, 241,242. 5 In the chapter on L 'Enfant et les Sortileges where the following is used: 34/2/1 it denotes page/ bar/ beat. The complete orchestral score of the selected scene can be found in Appendix A. The complete score of the Chansons madécasses can be found in Appendix B, (p.78 onwards), but musical examples in this chapter are included at relevant points since the cycle is rather extensive and cross-references occur frequently. These musical examples provide short illustrations. If further illustration of the musical point being made is needed, the reader is directed to the complete example in Appendix B by a figure in square brackets. For example; Mus. ex. 15: """"Nahandove"""" mm 46-48 [to 51]. Ravel remarked in an interview with De Telegraaf on March 31, 1931: """" Like Debussy and other contemporaries, I have always been particularly fascinated by musical orientalism. . . """"` and therefore it is hoped that in this dissertation, Ravel's relentless search for clarity of expression, as well as his innate artistic conscience is dutifully exposed, because he created an art of uncommon integrity, lucidity and excellence. As Arbie Orenstein, the noted Ravel scholar claims in his Ravel Reader : . like any other significant artist, Ravel fashioned his own laws and created his own universe : his Swiss-Basque heritage and Parisian sophistication, his subtle humour, his fascination for travel and exoticism, his interest in animals and children and his keen observations of nature are mirrored in his art, as are the disorientation and tragedy of World War One. Behind all these multificatious threads lies the composer's sovereign conscience and, in the words of Tristan Klingsor : the ironic and tender heart which beats under the velvet vest of Maurice Ravel.** * Arbie Orenstein. A Ravel Reader. New York: O.U.P., 1990, 473. ** Orenstein. Ravel Reader, 25.